Public libraries for children in architectural terms - Walczak-Niewiadomska, Agata (Folia Toruniensia, 2021)
The issue of architecture of buildings intended for the public libraries regularly appeared on the pages of Polish and foreign scientific and professional periodicals. However, it was not often that the authors raised the topic in the context of space for the youngest category of readers – children. This work complements the state of knowledge in the Polish literature on the subject by presenting changes that have taken place over the years in the approach to designing buildings and interiors of public libraries for children.